Effect of Yeast Species on Total Soluble Solids, Total Polyphenol Content and Fermentation Index during Simulation Study of Cocoa Fermentation - Teng-Sin, O.; Sepiah, M.; Khairul Bariah, S. (IJISET, 2016)
The polyphenols has potential of health beneficial and its changes in cocoa are related to fermentation index. However, relationship of yeast species to total soluble solids, total polyphenols and fermentation index changes during cocoa fermentation is still unclear. This study focused on effect of yeast as starter culture during cocoa fermentation towards those parameters. Sixteen species of yeast were used as starter cultures during simulation study of cacao fermentation in the laboratory. Study revealed that Candida ethanolica give the highest correlation with fermentation index whereas Candida jaroonii is the lowest correlation. None of the yeast species showed high correlation with total polyphenols content compared to the control. Conversely, all of the yeasts especially Pichia kudriavzevii showed higher correlation with total soluble solids compared to control. The study also exhibited that cacao simulation media method can be useful to predict yeast performance during cacao fermentation prior to field application.